The Determinant Analysis Of Socio Economic Status To Accounting Learning Outcome In Upi “Yptk” College Students - Susy Yuliastanty (Fakultas Sastra Universitas Ekasakti, 2017)
This study aims to analyze (1) the influence of head of household education on accounting learning outcomes, (2) the influence of family head work on accounting learning outcomes, (3) the influence of head of household income on accounting learning outcomes, (4) the influence of family demographics on learning outcomes Accounting (5) the influence of the environment on the learning outcomes of accounting, (6) the influence of internal characteristics of children on the learning outcomes of accounting, (7) the influence of children's gender on accounting learning outcomes, (8) the influence of head of family education, Family demographics, environment, internal characteristics of children and child gender on accounting learning outcomes. This research type is descriptive associative, where population of this research is all student of UPI